Анализа повезаног ризика серумских ТРФ и ЛГП 2 и срчане функције код пацијената са коронарном болешћу срца: Серумски ТРФ и ЛГП 2 и срчана функција код ЦХД - Cui, Tianhao; Zhao, Shuai; Xia, Ying; Zhang, Yongfei; Li, Congsheng (Journal of Medical Biochemistry, 2026)
[Objective] To explore the correlation between serum T cell replacing factor (TRF) and liver glutathione peroxidase 2 (LGP2) levels in patients with coronary heart disease (CHD) and cardiac function. [Methods] From October 2023 to October 2025, 252 patients with CHD who visited our hospital were selected as the disease group, among whom 72 had NYHA cardiac function grade II, 124 had grade III, and 56 had grade IV. The control group consisted of an additional 240 healthy patients who had physical examinations at our institution over the same time period. The CHD patients’ baseline data was gathered. Enzyme-linked immunosorbent assays were used to evaluate the blood levels of TRF, LGP2, brain natriuretic peptide (BNP), and creatine kinase isoenzyme (CK-MB) in each patient group. A color scale was used to quantify the left ventricular ejection fraction (LVEF), left ventricular end-systolic diameter (LVESD), left ventricular end-diastolic diameter (LVEDD), cardiac output (CO), interventricular septal thickness (IVS), and left ventricular mass (LV mass) of the CHD patients. Doppler ultrasound diagnostic apparatus. The relationship between blood TRF and LGP2 levels and cardiac function markers in CHD patients was examined using Pearson correlation analysis. [Results] The disease group’s systolic blood pressure and LDL-C levels were considerably greater than those of the control group, although serum TRF, LGP2, and HDL-C (high-density lipoprotein cholesterol) levels were significantly lower in the disease group (P<0.05). Serum BNP and CK-MB levels were considerably higher in the illness group than in the control group, and the LVESD, LVEDD, LV mass, and IVS were all significantly higher, while the LVEF and CO were significantly lower than those of the control group (P<0.05). NYHA-related cardiac function grade IV CHD patients had significantly lower LVEF, CO, and serum TRF and LGP2 levels than grade III and II patients did, and the LVEF, CO, and serum TRF and LGP2 levels of grade III CHD patients were significantly lower than those of grade II patients were, and the differences were statistically significant (P<0.05); NYHA-related cardiac function grade IV patients had significantly greater LVESD, LVEDD, LV mass, and IVS than grade III and II patients were, and the serum BNP and CK-MB levels were significantly greater than those of grade III and II patients were (P<0.05). The LVESD, LVEDD, LV mass, and IVS of grade III CHD patients were significantly greater than those of grade II patients, and the serum BNP and CK-MB levels were significantly greater in grade III CHD patients than in grade II patients (P<0.05). Serum TRF and LGP2 levels in patients with CHD were negatively correlated with serum BNP levels, CK-MB levels, LVESD, LVEDD, LV mass, and IVS (P<0.05) and positively correlated with LVEF and CO (P<0.05). [Conclusion] The serum levels of TRF and LGP2 in patients with CHD were significantly decreased, and both were closely related to cardiac function indicators.